2020
DOI: 10.1002/cmdc.202000831
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Nanomaterials for Smart Tumor‐Specific Phototherapeutics

Abstract: Phototherapy, a type of photoresponsive regulation of biological activities, together with additional stimuli‐responsive features, offers significant potential for enhancing the precision and efficacy of cancer treatments. To achieve tumor‐specific therapeutics, numerous studies have focused on the development of smart phototherapeutic nanomaterials (PNMs) that can respond to endogenous pathological characteristics (e. g., mild acidity, the overproduction of glutathione, the overproduction of hydrogen peroxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 138 publications
(283 reference statements)
0
3
0
Order By: Relevance
“…Phototherapeutics, a next-generation therapeutic modality, is a type of photoresponsive regulation of biological function and relative stimuli-responsive features, which thus supplies promising prospective for promoting the accuracy and efficacy of cancer treatments via producing reactive oxygen species (ROS) by photosensitizers and eliminating cancer cells by specific wavelength light irradiation [66,67]. Generally, phototherapeutics can be divided into three typical categories including photobiomodulation (PBM), photodynamic therapy (PDT), and photothermal therapy, which are widely applied to cancer administration such as colorectal cancer, head and neck cancer, breast cancer, and colorectal cancer [68,69].…”
Section: Nanomaterials In Cancer Phototherapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phototherapeutics, a next-generation therapeutic modality, is a type of photoresponsive regulation of biological function and relative stimuli-responsive features, which thus supplies promising prospective for promoting the accuracy and efficacy of cancer treatments via producing reactive oxygen species (ROS) by photosensitizers and eliminating cancer cells by specific wavelength light irradiation [66,67]. Generally, phototherapeutics can be divided into three typical categories including photobiomodulation (PBM), photodynamic therapy (PDT), and photothermal therapy, which are widely applied to cancer administration such as colorectal cancer, head and neck cancer, breast cancer, and colorectal cancer [68,69].…”
Section: Nanomaterials In Cancer Phototherapeuticsmentioning
confidence: 99%
“…Additionally, several kinds of nontoxic photosensitizers involved in phototherapy are also functionalized on the aforementioned carbon-based nanomaterials. Current research has also highlighted the potential role of stimuli-responsive nanomaterials (PNMs) with characteristics of responding to endogenous pathological changes for smart tumor-specific phototherapeutics [66]. For instance, Fu et al took advantage of the porous shuttle-shape platinum methylene blue (IV-Mb) coordination polymer nanotheranostics-loaded 10-hydroxycamptothecin (CPT) for synergistically enhancing the in situ mitochondrial reactive oxygen species (ROS) and highly efficient tumor ablation by phototherapy, which was regarded as a promising method for synergistic oncotherapy [70].…”
Section: Nanomaterials In Cancer Phototherapeuticsmentioning
confidence: 99%
“…These types of reactions can effectively improve the physicochemical properties, cellular uptake, and pharmacokinetic profile of PNMs. Additionally, the potential challenges and future directions in the development of PNMs are also presented incentivized to support the development of this new research area as shown in Figure 7 83,84 …”
Section: Smart Nanomaterialsmentioning
confidence: 99%